2019
DOI: 10.22207/jpam.13.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sensitivity of Bacterial Urinary Tract Infection among Adult Diabetic Patients in Misan Province, Iraq

Abstract: Urinary tract infections and their complications causing serious health problems especially in diabetic patients in Misan province, it is essential to determine the causative agent for appropriate treatment of this disease. One hundred and fifty urine samples were taken from adult patients with diabetes. The microbial growth appeared in 106 (70.6%) samples. Axenic culture was 83% versus 17% mixed growth. UTI prevalence was 65% with females comparing 35% of males and it was 56.6% in age group 35-49 years. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
6
10
0
Order By: Relevance
“…Female gender was mere susceptible to UTI in all investigated groups. The results are compatible with a previous study by Al-Tulaibawi (2019) in Misan province, Iraq, which showed that diabetic females are more susceptible to UTI. Seemingly the same results were concluded by (Alhamdany, 2018) at Babylon province .Also the same results were reported by (Taher et al, 2021) at Al-Kut province.…”
Section: Table (2):gender Distribution Of Patients and Healthysupporting
confidence: 92%
See 1 more Smart Citation
“…Female gender was mere susceptible to UTI in all investigated groups. The results are compatible with a previous study by Al-Tulaibawi (2019) in Misan province, Iraq, which showed that diabetic females are more susceptible to UTI. Seemingly the same results were concluded by (Alhamdany, 2018) at Babylon province .Also the same results were reported by (Taher et al, 2021) at Al-Kut province.…”
Section: Table (2):gender Distribution Of Patients and Healthysupporting
confidence: 92%
“…The leading isolated uropathogen was E. coli which in line with previous study by Al-Tulaibawi (2019) in Misan province , which showed the supremacy of E.coli over the other causative agents in regards to urine samples. Furthermore, agrees with the same terms as Tektook and Al-Lehibi, (2017)at the specialized center For endocrinology and diabetes of Baghdad city, Iraq.…”
Section: Table (2):gender Distribution Of Patients and Healthysupporting
confidence: 85%
“…The results of the present study corresponded to the result reported in Duhok Iraq [10] confirming that the majority (80.6%), of the microorganisms were Gram-negative. Furthermore, the results also corresponded with [11,12] who have ensured that UTI are common infections caused by bacteriuria. Previous studies in Iraq [13] and [14] also found that E. coli is the most common pathogen, which is associated with both community-and hospital-acquired UTI in many countries.…”
Section: Discussionsupporting
confidence: 77%
“…For one reference, no full paper was retrieved, and two papers did not deal with safety concerns. Three papers had serious methodological problems in relation to strain identification and source attribution and were not food related (Al-Tulaibawi, 2019;Nad aș et al, 2019;. Al-Tulaibawi (2019) described the isolation of B. subtilis from a urinary tract infection of diabetic patients; Thanganadar The ELS did not come up with any information that would change the status of the Bacillus species included in the QPS list and confirmed the qualification 'absence of cytotoxicity'.…”
Section: 32mentioning
confidence: 99%